Improving the Services Quality of Educational Staff Based on Satisfaction and Loyalty Analysis of Nursing Students - Fresty Africia; Stefanus Supriyanto; Tiyas Kusumaningrum (Universitas Airlangga, 2017)
Introduction: Educational staff services play a role in determining the quality of education. Service quality is able to provide satisfaction for students. Students who were satisfied with the perceived quality will develop student loyalty to the institution. The purpose of this study was to assess the effect of educational staff service quality with the satisfaction and loyalty of nursing students so that the educational institutions as service providers are able to provide the best service and survive in the midst of competition.Method: The study was an explanative survey with a cross-sectional design. Data collection was conducted using both quantitative (questionnaires) and qualitative (Focus Group discussion/FGD) methods. This study used proportional random sampling, with 110 students as samples. The variables in this research were customer expectations, perceived quality, student satisfaction and loyalty. The data was collected by a questionnaire and analyzed by linear regression, while FGD was conducted in two different groups (students and staff’s managers).Result: The result of the study explains the influence of student expectations on the perceived quality of the educational staff with a p-value = 0,002. There was no influence of student expectation on student satisfaction with a p-value = 0,156. The influence of the perceived quality of the educational staff towards student satisfaction had a p-value = 0,000. The influence of student satisfaction on student loyalty had a p-value = 0,000.Conclusion: The fulfilment of student expectations will have a positive impact on perceived quality. Furthermore, the positively perceived quality will create student satisfaction and student loyalty towards the educational institutions. For further research, it is suggested to examine the effect of satisfaction on student complaints.